2004
DOI: 10.1523/jneurosci.2265-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Synthase (NOS)-Interacting Protein Interacts with Neuronal NOS and Regulates Its Distribution and Activity

Abstract: Mechanisms governing the activity of neuronal nitric oxide synthase (nNOS), the major source of nitric oxide (NO) in the nervous system, are not completely understood. We report here a protein-protein interaction between nNOS and NOSIP (nitric oxide synthase-interacting protein) in rat brain in vivo. NOSIP and nNOS are concentrated in neuronal synapses and demonstrate significant colocalization in various regions of the central and peripheral nervous systems. NOSIP produces a significant reduction in nNOS acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 56 publications
(87 reference statements)
1
52
0
Order By: Relevance
“…On the other hand, these data may also suggest that elevations in [Ca 2ϩ ] i and nNOS dephosphorylation are required but not sufficient to induce nNOS activation and NO production and that other unknown PKA-dependent mechanisms are required for these processes. For instance, it has been demonstrated that NOSinteraction protein (NOSIP) interacts with and inhibits nNOS (Dreyer et al, 2004). The fact that NOSIP contains the consensus sequence for PKA supports the idea that PKA may [Ca 2ϩ ] i and NO production in hypothalamic neurons.…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, these data may also suggest that elevations in [Ca 2ϩ ] i and nNOS dephosphorylation are required but not sufficient to induce nNOS activation and NO production and that other unknown PKA-dependent mechanisms are required for these processes. For instance, it has been demonstrated that NOSinteraction protein (NOSIP) interacts with and inhibits nNOS (Dreyer et al, 2004). The fact that NOSIP contains the consensus sequence for PKA supports the idea that PKA may [Ca 2ϩ ] i and NO production in hypothalamic neurons.…”
Section: Discussionmentioning
confidence: 88%
“…Another protein that inhibits NO productions is nitric oxide synthase interacting protein (NOSIP) [29]. NOSIP and nNOS co-localize in different areas of the central and peripheral nervous systems.…”
Section: Nnos Inhibitorsmentioning
confidence: 99%
“…Of the three NO synthese isoforms, nNOS is mainly localized in the central nervous system, postsynaptic density (PSD), and muscular sarcolemma (muscle fiber myelin) and participates in neural transmission [39][40][41]. iNOS is usually not expressed, but is induced in vascular smooth muscle cells and macrophages via cytokine stimulation during sepsis or ischemia with or without reperfusion, and produces large quantities of NO [42].…”
Section: Discussionmentioning
confidence: 99%